2020
DOI: 10.1111/cns.13449
|View full text |Cite
|
Sign up to set email alerts
|

Altered amplitude of low‐frequency fluctuations and regional homogeneity in drug‐resistant epilepsy patients with vagal nerve stimulators under different current intensity

Abstract: Background The mechanisms of vagal nerve stimulation (VNS) for the treatment of drug‐resistant epilepsy (DRE) remain unclear. This study aimed to measure spontaneous brain activity changes caused by VNS in DRE patients using resting‐state functional MRI (rs‐fMRI). Methods The rs‐fMRI scans were performed in 16 DRE patients who underwent VNS surgery. Amplitude of low‐frequency fluctuations (ALFF) and regional homogeneity (ReHo) was generated and examined using paired sample t‐test to compare activity changes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…Subsequently, it should be noted that before ALFF calculation, fMRI images were spatially smoothed with full-width at half maximum (FWHM) 6 mm × 6 mm × 6 mm Gaussian kernel [ 44 ]. Before ReHo calculation, fMRI images were temporally band-pass filtered (0.01–0.08 Hz) to reduce low frequency drift and physiological high frequency respiratory and cardiac noise [ 8 , 45 ], and we didn’t perform spatial smoothness before ReHo calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it should be noted that before ALFF calculation, fMRI images were spatially smoothed with full-width at half maximum (FWHM) 6 mm × 6 mm × 6 mm Gaussian kernel [ 44 ]. Before ReHo calculation, fMRI images were temporally band-pass filtered (0.01–0.08 Hz) to reduce low frequency drift and physiological high frequency respiratory and cardiac noise [ 8 , 45 ], and we didn’t perform spatial smoothness before ReHo calculation.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that several kinds of multiple comparison correction strategies on statistical maps of ALFF and ReHo were carried out to increase test-retest reliability. The first strategy was a two-tailed GRF correlation with a single-voxel threshold of p < 0.001 and cluster-defining threshold of p < 0.05 [ 45 , 48 , 49 ]. The second method was an FDR correction ( p < 0.05) [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…If yes, it would be safer and more convenient to achieve therapeutic effects than current used invasive therapies such as deep brain stimulation and vagal nerve stimulation. 38 , 39 In summary, music adjuvant therapy could enhance the anti‐seizure efficacy of sub‐dose AEDs and provide a promising and convenient noninvasive adjuvant therapy for TLE.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the desirable adjuvant therapeutic effect on kindled seizures has been observed, we can optimistically speculate that patients with drug‐resistant TLE may also benefit from music adjuvant therapy. If yes, it would be safer and more convenient to achieve therapeutic effects than current used invasive therapies such as deep brain stimulation and vagal nerve stimulation 38,39 . In summary, music adjuvant therapy could enhance the anti‐seizure efficacy of sub‐dose AEDs and provide a promising and convenient noninvasive adjuvant therapy for TLE.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the stimulation of the vagus nerve can improve the mood, consciousness, and memory in some patients, and thus further improve the quality of life in epileptic patients. It has been internationally recognized as a safe and effective treatment for children and adults with local and comprehensive intractable epilepsy, and its adaptive population is continuously increasing 102,104,110,111,113,114 …”
Section: Potential Alternative Therapies For Drug‐resistant Focal Epilepsymentioning
confidence: 99%